A TRAINING MATERIAL: A SOLUTION TO HELP FRONT OFFICE STAFFERS AND ATTRACT MORE CUSTOMERS FOR IBIS SURABAYA CITY CENTER HOTEL - Fransisca Vina Esterina; Samuel Gunawan (Institute of Research and Community Outreach - Petra Christian University, 2015)
This thesis is related to the Front Office staffers of ibis Surabaya City Center Hotel who have difficulties in giving information and handling complaints from overseas guests. Therefore, they need a training material in English that contains three lessons about giving information, handling complaints, and receiving calls. This training material is equipped with conversations, sentence pattern and substitution, list of important words, exercises, and also answer key to help the Front Office staffers to have better performances in terms of customer service. By having this training material, ibis Surabaya City Center Hotel will gain three benefits. Firstly, this training material will help the Front Office staffers at ibis Surabaya City Center Hotel to support their work performance. Secondly, this training material can help the Front Office staffers to improve their English skill since it is written in English. Finally, this training material can help Front Office staffers to give the best possible service to the hotel’s guests.